Highly efficient extraction of uranium from seawater by polyamide and amidoxime co-functionalized MXene. (15th January 2023) - Zhang, Di; Liu, Lijie; Zhao, Bing; Wang, Xiangxue; Pang, Hongwei; Yu, Shujun
Abstract: Uranium mainly exists in the form of uranyl carbonate in seawater. [UO2 (CO3 )3 ] 4- has strong stability, which increases the difficulty of uranium extraction from seawater. Meanwhile, the complex marine environment, a large number of coexisting competing ions and biological pollution are all non-negligible disturbing factors. Herein, we introduced amidoxime (AO) groups into the surface of Ti3 C2 and grafted polyamides (PA) by a simple one-step hydrothermal method to produce an efficient seawater uranium extraction adsorbent Ti3 C2 -AO-PA. Owing to the amidoxime groups, the material was highly selective for uranium. And the large number of amino groups in the polyamides gave it ideal resistance to biofouling. The possibility of Ti3 C2 -AO-PA as an adsorbent for uranium extraction from seawater was confirmed by various characterization techniques, numerous adsorption batch experiments, simulated seawater experiments and antibacterial performance tests. It was demonstrated that the uptake of [UO2 (CO3 )3 ] 4- by Ti3 C2 -AO-PA showed fast reaction kinetics (about 120 min), brilliant absorption capacity (81.1 mg·g −1 at pH 8.3), significant high selectivity (32.8 mg-U/g-Ads) and outstanding anti-biological contamination performance (92.9% antibacterial rate). XPS and DFT further indicated that the high extraction ability of Ti3 C2 -AO-PA for uranium was mainly attributed to the strong complexation of AO and –NH2 with [UO2 (CO3 )3 ] 4- . These conclusions showed that Ti3 C2 -AO-PA not only had an ideal application prospect for uranium extraction from seawater, but also provided an available strategy for rapid and selective uranium adsorption from real seawater. Graphical abstract: Image 1 Highlights: Polyamide enhanced amidoxime-functionalized Ti3 C2 nanosheet was constructed. The uranium extraction capacity was highly enhanced. Ti3 C2 -AO-PA showed excellent selectivity and antimicrobial properties. Synergistic interactions of amidoxime and polyamide with uranium ions in seawater.